LEGAL ASPECTS OF ENSURING RIGHTS, FREEDOMS AND LEGITIMATE INTEREST OF PERSONS, CONVICTED TO DEPRIVATION OF LIBERTY IN UKRAINE - Чеботарьова, Юлія Анатоліївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
A comparative legal analysis of the rights, freedoms and legitimate interests of persons sentenced toimprisonment in Ukraine, gives an overview of the state of compliance of national legislation on this majorinternational legal acts and decisions of the European Court of Human Rights, argues the need for reform ofpenal legislation.